2020
DOI: 10.1186/s13690-020-00486-z
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition and associated factors among adult HIV/AIDS patients receiving antiretroviral therapy in eastern zone of Tigray, Northern Ethiopia: a cross-sectional study

Abstract: Background Undernutrition and HIV/AIDS are highly prevalent in sub-Saharan Africa, Ethiopia inclusive as linked in a vicious cycle. Thus, several studies have documented that undernutrition among HIV/AIDS patients increases the risk of mortality, decrease survival rates, affect the overall clinical outcome and quality of life. Despite this fact, information about the burden of undernutrition and associated factors among adults receiving antiretroviral therapy is lacking in the particular study area. Hence, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 26 publications
6
23
1
Order By: Relevance
“…The prevalence of undernutrition found in our study was comparable with the previous study findings from different areas of Ethiopia like in Wolayita Sodo Hospital 26.6% [21], Nekemte referral hospital 27% [13], Butajira hospital 25.2% [22], and Bahir Dar Hospital 25.5% [23]. However, our findings was lower than previous studies like 46.8% in Jimma Hospital southwest Ethiopia [12], 42.3% in Tigray, northern Ethiopia [24], 30% in East Hararghe Zone Hospitals, eastern Ethiopia [25], 73% in India [26], and 57% in Malawi [27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of undernutrition found in our study was comparable with the previous study findings from different areas of Ethiopia like in Wolayita Sodo Hospital 26.6% [21], Nekemte referral hospital 27% [13], Butajira hospital 25.2% [22], and Bahir Dar Hospital 25.5% [23]. However, our findings was lower than previous studies like 46.8% in Jimma Hospital southwest Ethiopia [12], 42.3% in Tigray, northern Ethiopia [24], 30% in East Hararghe Zone Hospitals, eastern Ethiopia [25], 73% in India [26], and 57% in Malawi [27].…”
Section: Discussionsupporting
confidence: 91%
“…The multivariate analysis result of our study revealed that male patients have higher odds of having undernutrition as compared to those female patients (AOR 2.11, 95%CI: 1.34, 3.12) and the finding was consistent with the previous study findings in Ethiopia and other African countries [21,23,30]. This result could be due to different possible justifications.…”
Section: Discussionsupporting
confidence: 90%
“…The nding was lower when compared with study conducted in Brazil (46%) (17), study conducted in Kenya (29%) (18), Tanzania (27%) (20), study reported from Tigray region (42%) (21), study reported from Jimma(34%)(23), Southern Ethiopia (23.72%) (46) and Silte Zone(24.1%) (15).…”
Section: Discussionmentioning
confidence: 73%
“…The sample was taken by simple random sampling from those who t the criteria. Adherence to ART drug: It was assessed using Morisky medication adherence score to ART drug having eight questions each with yes = 1 and no = 2, good adherence for those score 7-8, and poor adherence for those score ≤ 6 (21).…”
Section: Sampling Methodsmentioning
confidence: 99%
See 1 more Smart Citation